(3TQM bhGYO GdEYQGHs - (3CHh GdKfGA CMeO Hf eMeO GdRjdis; (3CHh eMeO LeGd GdOjf YHO Gddg Hf jhSa GHf gTGe GdfMhj,J (B762 (3g` s ((3Ydi Hf YeQ GdfMja s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY CSeGA GdYdeGA HaYd GdNTjI ai bhdg (B( (3EfeG fNTi Gddg ef YHGOg GdYdeGA (B) (3hfhQ HeUHGM eYGQage GdcGajI bdhH GdWGdHjf fMhg s
(3BNQgG (B:s
(3hai GdNGJeI GdcGajI gPG BNQ eG JjSQ dfG EjQGOg HMeO Gddg hefg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs